2021
DOI: 10.1021/acs.inorgchem.1c01511
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Synthetic Strategy for the Preparation of Heteroleptic Metallacycles of Porphyrins

Abstract: We present a stepwise synthetic strategy for the preparation of the unprecedented heteroleptic 2+2 neutral metallacycle [{ t,c,c -RuCl 2 (CO) 2 } 2 (4′ cis DPyP)(3′ cis DPyP)] ( 5 ), in which two different 5,10- meso -dipyridylporphyrins, 4′ cis DPyP [i.e., 5,10-bis(4′-pyridyl)-15,20-diphenylporphyrin] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 57 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…As always observed by us in the past for previous porphyrinÀ Ru neutral assemblies (see Refs. [46][47][48]), the ESI-MS spectra of the model complexes and metallacycles of porphyrins only showed peaks deriving from the fragmentation (ESI mass spectra were collected in the positive mode on a Perkin-Elmer APII spectrometer at 5600 eV). No molecular ion peak could be detected despite the many attempts.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As always observed by us in the past for previous porphyrinÀ Ru neutral assemblies (see Refs. [46][47][48]), the ESI-MS spectra of the model complexes and metallacycles of porphyrins only showed peaks deriving from the fragmentation (ESI mass spectra were collected in the positive mode on a Perkin-Elmer APII spectrometer at 5600 eV). No molecular ion peak could be detected despite the many attempts.…”
Section: Methodsmentioning
confidence: 99%
“…As a proof of concept, the novel 2+2 heteroleptic neutral metallacycle [{ t , c , c ‐RuCl 2 (CO) 2 } 2 (4′ cis DPyP)(3′ cis DPyP)] ( 1 ) was prepared by us in pure form and acceptable isolated yield through two complementary stepwise modular approaches that exploited the ditopic reactive intermediates [{ t , c , c ‐RuCl 2 (CO) 2 (dmso‐O)} 2 (4′ cis DPyP)] or [{ t , c , c ‐RuCl 2 (CO) 2 (dmso‐O)} 2 (3′ cis DPyP)] (Scheme 1). [46] Remarkably, we found that the alternative one‐pot synthetic strategy, i. e. the addition of two equiv. of the ruthenium precursor [ t , c , c ‐RuCl 2 (CO) 2 (dmso‐O) 2 ] to a 1 : 1 mixture of 4′ cis DPyP and 3′ cis DPyP, was substantially ineffective for the preparation of 1 in pure form.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations